Pengaruh Kepemilikan Institusional, Dewan Komisaris Independen, Kepemilikan Manajerial dan Intensitas Persedian Terhadap Agresivitas Pajak (Studi Empiris pada Perusahaan Makanan dan Minuman yang terdaftar di Bursa Efek Indonesia Periode Tahun 2016-2019) - Pratama, Irfan; Rina Asmeri; Andre Bustari (Ekasakti Pareso Jurnal Akuntansi, 2023)
This study aims to determine the effect of Institutional Ownership, Independent Board of Commissioners, Managerial Ownership and Inventory Intensity on Tax Aggressiveness in Food and Beverage Companies listed on the Indonesia Stock Exchange 2016-2019. The type of statistics used in this have a look at is quantitative records taken from the Indonesia inventory exchange. The population in this study are Food and Beverage Companies listed on the Indonesia Stock Exchange in 2016-2019, as many as 38 companies. The sample in this study was 10 samples taken through purposive sampling method. The analytical method used in this research is multiple linear regression analysis with classical assumption test using SPSS 25.0 application. The results of this study indicate that the influence of institutional ownership and managerial ownership partially has no significant effect on tax aggressiveness in food and beverage companies. The influence of the Independent Board of Commissioners partially has a positive effect and the Influence of Inventory Intensity partially has a significant negative effect on Tax Aggressiveness in Food and Beverage Companies. Simultaneously the influence of institutional ownership, independent board of commissioners, managerial ownership and inventory intensity have a significant effect on aggressive decisions.